1997
DOI: 10.1007/pl00005122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TMK688, a novel anti-allergic drug, on allergic nasal obstruction and exudative responses in sensitized guinea pigs

Abstract: TMK688 (1-[[5'-(3"-methoxy-4"-ethoxycarbonyloxyphenyl)-2',4'-pentadien oyl] aminoethyl]-4-diphenylmethoxypiperidine) is being developed as an orally effective antiallergic drug having both 5-lipoxygenase inhibitory activity and anti-histamine activity (Shizawa et al. 1996; Tohda et al. 1997). The efficacy of TMK688 against allergic rhinitis was examined in passively sensitized guinea pigs. TMK688 inhibited the increase in intranasal resistance following antigen challenge at doses of 1 and 3.2 mg/kg p.o. The al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Intranasal pressure was measured as an index of intranasal resistance by the method described in previous papers [14, 15]with minor modifications. Briefly, guinea pigs were anesthetized with urethane (1.6 g/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Intranasal pressure was measured as an index of intranasal resistance by the method described in previous papers [14, 15]with minor modifications. Briefly, guinea pigs were anesthetized with urethane (1.6 g/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…That is, the experimental animals also exhibit sneezing [6][7][8][9][10] , nasal secretion [9] and nasal obstruction [6][7][8][9][10][11][12][13][14][15][16][17] . It has been demonstrated that histamine [10,12,14,16] , leukotrienes [9,10,12,13,16] , and thromboxane [6,10,12,14,15,17,18] are involved in the mechanism of development of the pathology in these models. Accordingly, these guinea pig models have come to be widely used for evaluation of the pharmacological effects of drugs being developed for the treatment of allergic rhinitis.…”
mentioning
confidence: 99%